2023
DOI: 10.1055/s-0043-1774319
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Candida albicans Adhesion and Related Surface Properties of CAD/CAM Denture Base Resins

Shaimaa M. Fouda,
Mohammed M. Gad,
Reem Abualsaud
et al.

Abstract: Objective The aim of this study was to evaluate the surface roughness, contact angle, and adhesion of Candida albicans to computer-aided designing/computer-aided manufacturing (CAD/CAM) and heat-polymerized (HP) denture base materials. Materials and Methods Specimens were allocated to six groups based on the composition of studied denture base materials, HP acrylic resin, milled resins (AvaDent and IvoCad), and 3D-printed resins (ASIGA, FormLabs, and NextDent). Ten specimens per group were used for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the present study, all test materials showed similar contact angle values. Contrary to these results, Fouda et al [21] reported that the contact angles of milled resins were significantly lower than those of heat and 3D-printed resins. Alammari [36] observed that the polymerized CAD/CAM acrylic resin denture base materials had low contact angles (about 67 to 70°), which suggests good wettability.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In the present study, all test materials showed similar contact angle values. Contrary to these results, Fouda et al [21] reported that the contact angles of milled resins were significantly lower than those of heat and 3D-printed resins. Alammari [36] observed that the polymerized CAD/CAM acrylic resin denture base materials had low contact angles (about 67 to 70°), which suggests good wettability.…”
Section: Discussionmentioning
confidence: 77%
“…The right and left static contact angles were then measured as soon as a single water droplet touched the sample's center on both sides. Each drop and the disk surface were photographed, and the water contact angle was recorded [19,21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study ( 5 ) found that milled and 3D printed denture base materials were biocompatible and had similar surface characteristics. Fouda et al ( 20 ), found that there was no difference in surface roughness between 3D printed, milled, and conventional rein, and that the adherence of C. albicans to all resins behaved similarly. Due the variations in surface properties of denture base resins and amount of microbial adhesions, authors suggested evaluating different CAD-CAM systems with different resins materials.…”
Section: Introductionmentioning
confidence: 99%